Increasing the Addition of Two Total Numbers Learning Results Through The Problem Based Learning (PBL) Model Assisted By Visual Audio Media In SD Students - Sri Wilujeng (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of Classroom Action Research (CAR) is to solve real problems that occur in the classroom so that it can improve and improve the quality of learning. This PTK generally aims to improve the learning outcomes of grade III students in mathematics subject matter at SD Negeri 02 Banjarsari Pemalang. To achieve optimal results, teachers need to use a learning model that can help students relate subject matter to real life, so that learning becomes more meaningful. This model is the Problem Based Learning (PBL) model. The results showed an increase in student learning outcomes from cycle I to cycle II. In the first cycle, the average value of student learning outcomes reached 77.78 and the percentage of completing classical learning was 77.78%, while in the second cycle the average value increased to 84.44 and the percentage of completing classical learning became 88.89%. Based on these results, it can be concluded that the PBL model assisted by audio-visual media can improve student learning outcomes. Teachers can use the PBL model as an alternative learning model to improve the quality of learning in schools.